2019
DOI: 10.1111/bjd.18338
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course of actinic keratosis correlates with underlying molecular mechanisms

Abstract: Summary Background Actinic keratoses (AKs) are common premalignant skin lesions triggered by excessive ultraviolet exposure. The majority of AKs regress or persist, but some progress to squamous cell carcinomas. Biomarkers associated with their persistence, progression and regression have not been characterized. Objectives We performed skin biopsies in patients with extensive actinic damage to identify biomarkers that correlate with clinical progression and regression of AKs. Methods This was an observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
2
26
0
4
Order By: Relevance
“…22,23 The expression of p53 also decreased in regressed AK and non-sun-exposed skin compared with sun-exposed skin and clinically apparent AK. 24 Ishida et al and our findings demonstrated that p53 stained basal keratinocytes in AK and left them unstained in BD. 25 They assumed that attenuation and disappearance of the sparing of the basal keratinocytes is a sign of tumor progression.…”
Section: Discussionsupporting
confidence: 59%
“…22,23 The expression of p53 also decreased in regressed AK and non-sun-exposed skin compared with sun-exposed skin and clinically apparent AK. 24 Ishida et al and our findings demonstrated that p53 stained basal keratinocytes in AK and left them unstained in BD. 25 They assumed that attenuation and disappearance of the sparing of the basal keratinocytes is a sign of tumor progression.…”
Section: Discussionsupporting
confidence: 59%
“…[42] There is a growing interest in the development of of E-cadherin, and these were increased in AKs compared with normal sun-exposed skin. [43] Studies are ongoing to determine genes that can differentiate high-risk AKs from more indolent lesions that will not progress into SCCs, which will facilitate the identification of benign AKs to avoid unnecessary treatment of the 95% of AKs that will not develop into malignant cancerous lesions.…”
Section: Biomarker Of Risk Stratification Of Precancerous Lesionsmentioning
confidence: 99%
“…Actinic keratoses (AKs) are common dysplastic epidermal lesions resulting from chronic and excessive ultraviolet exposure [ 1 ]. AKs are more common in male sex, phototypes I and II, and in old age [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…AKs are more common in male sex, phototypes I and II, and in old age [ 2 , 3 ]. The majority of AKs persist, regress, or regress and relapse, but some progress to invasive squamous cell carcinomas (SCCs) [ 1 ]. The real risk of progression is difficult to quantify and has been variously estimated by different authors.…”
Section: Introductionmentioning
confidence: 99%